Prioritization of strategies to enhance the competitiveness of the halal food industry in Madura - Rum, Mokh; Kurniyanto, Ifan Rizky; Isaskar, Riyanti; Musyafak (Halal Studies and Society, 2025)
Madura holds potential for the development of the halal industry, supported by natural resources and a workforce. Competitiveness becomes a key factor in the success of the industry amidst free competition with other industries outside of Madura. Determining priority strategies to enhance the competitiveness of halal food requires a proper decision-making system involving experts. This research aimed to identify strategies to enhance the competitiveness of the halal food industry in Madura. The analytical method used was the analytical hierarchy process (AHP). The research focused on the food industry in Madura, and the informants consisted of experts in the development of halal food industries. The analysis results indicate the sequential priority strategies to enhance the competitiveness of the halal food industry in Madura: enhancing the competency of human resources in the halal food industry, setting quality production standards, building networks for marketing halal food, implementing halal value chains, obtaining halal certification, and utilizing Shariah-compliant financing.